Analysis of the Effectiveness of E-Learning in Enhancing English Comprehension Among Electrical Engineering Students: A Case Study in Cirebon" - Eliyawati, Eliyawati; Kurniawan, Zuki; Indriyani, Devia; Rosadah, Ros Awaliyah (Mestro: Jurnal Teknik Mesin dan Elektro, 2025)
This study aims to analyses the effectiveness of e-learning in enhancing the English comprehension of Electrical Engineering students in Cirebon. The research employs a quantitative method with a journal review approach to identify trends and the effectiveness of e-learning in English learning for engineering students. The findings indicate that e-learning significantly contributes to students' comprehension improvement, particularly in reading and listening skills. Students who actively use e-learning show a 30% increase in English comprehension scores compared to those who rely solely on conventional learning methods. A total of 75% of students reported that e-learning helped them better understand technical materials in English. However, challenges remain in student interaction and learning motivation, especially in speaking and writing skills. The conclusion of this study suggests that e-learning can be an effective learning medium with proper implementation strategies, including enhancing digital interaction and developing more engaging methods for students. REFERENCES Clark, R. C., & Mayer, R. E. (2016). E-Learning and the Science of Instruction: Proven Guidelines for Consumers and Designers of Multimedia Learning. John Wiley & Sons. Horton, W. (2006). E-learning by design. Pfeiffer Gok, T. (2016). The Effects of Social Networking Sites on Students’ Studying and Habits. International Journal of Research in Education and Science, 2(1), 85–93. Liaw, S. S., Huang, H. M., & Chen, G. D. (2007). Surveying instructor and learner attitudes toward e-learning. Computers & Education, 49(4), 1066-1080. https://doi.org/10.1016/j.compedu.2006.01.001 Rosenberg, M. J. (2001). E-learning: Strategies for delivering knowledge in the digital age. McGraw-Hill. Sun, P. C., Tsai, R. J., Finger, G., Chen, Y. Y., & Yeh, D. (2008). What drives a successful e-Learning? An empirical investigation of the critical factors influencing learner satisfaction. Computers & Education, 50(4), 1183-1202. https://doi.org/10.1016/j.compedu.2006.11.007 Universitas X. (2023). Laporan Survei Pemahaman Bahasa Inggris Mahasiswa Teknik Elektro. Penerbit Universitas X. Zhang, D., Zhou, L., Briggs, R. O., & Nunamaker, J. F. (2006) Instructional Video in E-Learning: Assessing the Impact of Interactive Video on Learning Effectiveness. Information & Management, 43(1), 15–27. Wu, J. H., Tennyson, R. D., & Hsia, T. L. (2015). A study of student satisfaction in a blended e-learning system environment. Computers & Education, 55(1), 155-164. Wu, W. H., Wu, Y. C. J., Chen, C. Y., Kao, H. Y., Lin, C. H., & Huang, S. H. (2015). Review of trends from mobile learning studies: A meta-analysis. Computers & Education, 59(2), 817–827. https://doi.org/10.1016/j.compedu.2012.03.016